Electro‐Optic Crystals: Fluorinated Organic Electro‐Optic Quinolinium Crystals for THz Wave Generation (Advanced Optical Materials 4/2019). Issue 4 (19th February 2019) - Kim, Se‐In; Kang, Bong Joo; Jeong, Chan‐Uk; Shin, Myeong‐Hoon; Kim, Won Tae; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract : In article number1801495, Fabian Rotermund, O‐Pil Kwon, and co‐workers report that fluorinated organic electro‐optic crystals providing state‐of‐the‐art macroscopic optical nonlinearity exhibit excellent THz wave generation characteristics with a significantly modulated THz spectral shape compared to nonfluorinated benchmark nonlinear optical organic crystals.